Coherence Relations in Primary School Textbooks: Variation across School Subjects. Issue 8 (17th November 2019) - Ibáñez, Romualdo; Moncada, Fernando; Cárcamo, Benjamín
ABSTRACT: The aim of this study was to compare the use of coherence relations in the school textbooks of four primary school subjects. A corpus of 1, 882 texts, corresponding to the genres used to teach in the school textbooks of Science, Language, Mathematics, and History, was analyzed. The analysis was performed manually using a taxonomy that incorporates and adapts criteria developed in the Cognitive approach to Coherence Relations and in the Connectivity Model. Results show that while some relations are used across school subjects (Conjunction, Concept Description), others are used almost exclusively in certain school subjects (Condition-Event in Science, Basic Contrast in History, Deictic in Language, and Condition-Question in Mathematics). Considering that types of coherence relations are different in terms of internal complexity, these results may represent relevant information for classroom instruction, primary school textbook design, and text comprehension research.